Molecular Study of Acinetobacter baumannii Isolates for Metallo-β-Lactamases and Extended-Spectrum-β-Lactamases Genes in Intensive Care Unit, Mansoura University Hospital, Egypt - Nashwa M. Alkasaby; Maysaa El Sayed Zaki (International Journal of Microbiology)
Acinetobacter baumannii (A. baumannii) has been known as a causative pathogen of hospital acquired infections. The aim of this study is to examine the presence of A. baumannii among clinical isolates from intensive care unit (ICU) in Mansoura University Hospital (MUH), its antibiotic resistance pattern, and prevalence of antibiotic resistance genes metallo-β-lactamases (MBLs) and extended-spectrum-β-lactamases (ESBLs) among A. baumannii isolates. A. baumannii was identified by colony morphology, API 20E, and confirmed by detecting the bla OXA-51-like carbapenemase gene by PCR. Phenotypic expression of MBLs resistance was demonstrated by Combined Disk Test (CDT) in 273 isolates (97.5%) and of ESBLs was demonstrated by double disc synergy method (DDST) in 6 isolates (2.1%). MBLs genes were positive in 266 isolates (95%) and ESBLs genes were positive in 8 isolates (2.9%). The most frequent genes of MBLs studied genes were IMP (95.7%) followed by SIM and GIM (47.1% and 42.9%; resp.). For ESBL genes, the most frequent gene was TEM (2.9%). From this study, we conclude that multidrug resistant (MDR) A. baumannii with MBLs activity was the most common isolate. Careful monitoring for the presence of MDR A. baumannii among hospitalized patients is recommended to avoid wide dissemination of antibiotic resistance.